Hepatitis E Virus Infection in Dromedaries, North and East Africa, United Arab Emirates, and Pakistan, 1983–2015 - Rasche, Andrea; Saqib, Muhammad; Liljander, Anne M.; Bornstein, Set; Zohaib, Ali; Renneker, Stefanie; Steinhagen, Katja; Wernery, Renate; Younan, Mario; Gluecks, Ilona; Hilali, Mosaad; Musa, Bakri E.; et al. (Emerging infectious diseases, 2016)
A new hepatitis E virus (HEV-7) was recently found in dromedaries and 1 human from the United Arab Emirates. We screened 2,438 dromedary samples from Pakistan, the United Arab Emirates, and 4 African countries. HEV-7 is long established, diversified and geographically widespread. Dromedaries may constitute a neglected source of zoonotic HEV infections.